The Bard’s Journey to the “Small time” in China (Altre Modernità, 2017)
Borrowing the term "small-time Shakespeare" coined by Christy Desmet (1999) and adopted by Alexander Huang (2004, 2009), this paper is concerned with the concept in its sense of signifying an individual, local, and pointed production approach, in contrast to Òbig-time ShakespeareÓ performances defined as institutionalized, corporate, and conservative by Michael Bristol (1996). Addressing the particular context of Mainland China in the 21st century, two categories of Òsmall-timeÓ Shakespeare are examined in this paper: 1. the ÒautobiographicalÓ category that, according to Huang, is adapter-centered to stress local and even personal interpretations; 2. the ÒanthropologicalÓ category that is viewed as plural, inclusive, and encompassing by Stephen Purcell (2009). The first is represented by Lin ZhaohuaÕs Shakespeare adaptations, while the second is represented by ÒRomeo and JulietÓ, a performance in a city square tailor-made for migrant workers in Beijing in 2006. Through a comparative examination of these two categories, the author argues that Shakespeare performances are undergoing a conspicuous shift from the Òbig-timeÓ to the Òsmall-timeÓ in China and so far as the particular socio-economic and cultural conditions are concerned, the ÒanthropologicalÓ Shakespeare better fits the context of China and better serves ordinary audiences than the ÒautobiographicalÓ.